Quantum and Classical Phases of the Pyrochlore Heisenberg Model with Competing Interactions - Yasir Iqbal; Tobias Müller; Pratyay Ghosh; Michel J. P. Gingras; Harald O. Jeschke; Stephan Rachel; Johannes Reuther; Ronny Thomale (Physical Review X, 2019)
We investigate the quantum Heisenberg model on the pyrochlore lattice for a generic spin S in the presence of nearest-neighbor J_{1} and second-nearest-neighbor J_{2} exchange interactions. By employing the pseudofermion functional renormalization group method, we find, for S=1/2 and S=1, an extended quantum-spin-liquid phase centered around J_{2}=0, which is shown to be robust against the introduction of breathing anisotropy. The effects of temperature, quantum fluctuations, breathing anisotropies, and a J_{2} coupling on the nature of the scattering profile, and the pinch points, in particular, are studied. For the magnetic phases of the J_{1}-J_{2} model, quantum fluctuations are shown to renormalize phase boundaries compared to the classical model and to modify the ordering wave vectors of spiral magnetic states, while no new magnetic orders are stabilized.